A Religious Tolerance and Harmony the Qur'anic Perspective - Choirul Fuad Yusuf (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2012)
The religious tolerance and harmony is something necessary to develop due to the need of global security and peace today. For this purpose, all religions have to be fairly “tolerant” to others. Islam as a revealed religion, whatever its motive, is often perceived and accused as the religion of intolerance and violence. Some political and ideological questions, for example raised to this context: "Can Islamic faith tolerate other faiths, religions or groups?”, What’s actually the Islamic teachings on tolerance and peace or harmony?” and the likes. This article attempts to unpack and elaborate of how far at Qur’an –as the first and primary source of Islam– has a teaching on tolerance and peace. Using a hermeneutical approach the writer understands and analyses what is actually taught by al Qur'an on the concepts and practices of the tolerance. Based on the analysis, he highlights any conclusions of which al-Qur’an (Islam) teaches the followers to respect and implement the doctrine of tolerance and peace. The Muslim world is imperatively to tolerate others, or respect the differences for strengthening the world security and peaceful life amongst nationwide.